Microform collections in selected research and academic libraries in Metro Manila a survey with implications for resource sharing - Shrestha, Ramila; Hidalgo, Namnama P.; Buenrostro, Juan Jr. C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1988)
The study aims to identify significant or dynamic microform collections in selected academic and research libraries in Metro Manila to determine the extent and nature of their microform collections and of microform resource sharing. This study was designed and carried out in October and November 1987.
The sample of the study is comprised by six academic libraries, five special libraries and ten government agency libraries.
The descriptive research method was used, utilizing preliminary and main questionnaires which were supplemented by interviews and documentary analysis. The preliminary questionnaire was distributed to find out the libraries having active microform programs while the main questionnaire was sent to the libraries having microform collections with active microform development programs. The chief librarians of the respondent libraries provided information for this study. Responses were tabulated and analyzed by frequency, percentage and ranking in accordance with the objectives of the study.
The study revealed that only one-fourth of the respondent libraries have large collections of microforms. Academic libraries have larger collections of microforms than special and government agency libraries. Almost all the respondent libraries have two types of microforms, i.e., microfilm and microfiche. Only the Office of Energy Affairs Data Bank and Library (OEADBL) has microcards in its microform collection. The special and government agency libraries have microforms in specialized subject areas. Only academic libraries and The National Library have microforms in a wide range of subject fields. Only ten libraries have separate budget allocations for microform collection. But all the respondents have inadequate financial resources. The collections of the respondent libraries are organized, with majority using the Anglo-American Cataloging Rules, second edition (AACR II). The microforms are arranged by subject or accession number in most of the libraries; four libraries only index their microforms.
Only academic libraries and The National Library have specific staff assigned to the microform collection. The internal and external users served by the respondent libraries are administrators, teachers, researchers and graduate and undergraduate students. Researchers and graduate students tend to use microform collections more than other user groups. Almost all respondent libraries serve external users. Use in the academic and research libraries is heavier than in the government agency libraries. Majority of libraries have well defined acquisition and public service policies regarding their microform collection but only few libraries have bibliographic control policy. Fifteen respondent libraries are involved in cooperative activities, mainly on informal basis; eight are sharing microforms in their cooperative activities. The majority of the respondent libraries perceive that microform resource sharing provides benefits such as effective information services, strengthened resources and collection development.
All the respondent libraries except two are willing to participate in microform resource sharing activities, particularly union listing of microform resources, interlibrary loan, cooperative acquisition, and providing duplicate copies. A plan is proposed for the collective development and expansion of microform resources in order to improve information service effectiveness within the limited financial resources of the participating libraries.
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: Libraries -- Special collectionsxMicroforms. -- Philippines -- Metro Manila; Library cooperation -- Philippines -- Metro Manila